Architecture, Mural Decoration and Pottery in Sirigu Culture - Wemegah, Rolland (2011)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirements for the Degree of Master of Arts (African Art and Culture)